Pullout behavior of vertical ground anchor in dry homogeneous sand at different relative densities / Mohd Rafe Abdul Majid and Ideris Zakaria - Abdul Majid, Mohd Rafe; Zakaria, Ideris (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Vertical ground anchors are commonly used in foundation systems for structures requiring pullout resistance such as transmission towers, structures requiring lateral resistance, such as sheet pile walls. The work described in this research is primarily concerned with the pullout capacity of a vertical ground anchor embedded in dry homogeneous sand. One-laboratory model of anchor test apparatus is fabricated, with dry sand as a medium in sand box to form the homogeneous sand bed. Three models of circular anchors namely 25, 50 and 75 mm diameter and three states of homogeneous sand bed with different unit weights i.e., 15.89, 16.29 and 17.13 kN/m3, where the relative densities are 29%, 37% and 53% respectively were used in this research. The range of depth/ diameter (D/B) ratios are from 1 to 24 in order to cover shallow and deep anchors with the anchors being subjected to vertical loads under displacement control. The results showed that the pullout behavior was influenced by the density of the embedded homogeneous sand and the depth of embedment. The results also showed that the pullout resistance behavior follows a similar curve until it reached a peak transition point where the trending of breakout factor diverged influenced by the depth of embedment and the homogeneous soil density. Overall, the study provides insights about pullout capacity of vertical ground anchor in homogeneous sand.